The Effect of Working Hours on Health - Berniell, Inés (2020)
Does working time affect workers' health behavior and health? We study this question in the context of a French reform that reduced the standard workweek from 39 to 35 hours, at constant earnings. Our empirical analysis exploits arguably exogenous variation in the reduction of working time across employers due to the reform. We find that the shorter workweek reduced smoking by six percentage points, corresponding to 16% of the baseline mean. The reform also appears to have lowered BMI and increased self-reported health, but these effects are imprecisely estimated in the overall sample. A heterogeneity analysis provides suggestive evidence that while the impact on smoking was concentrated among blue-collar workers, body mass index decreased only among white-collar workers. These results suggest that policies which reduce working time could potentially lead to important health benefits.